TEACHING ENGLISH VOCABULARY USING SONG - Adnyani, Ni Wayan Satri; Dewi, A.A.I. Bulan Fitria (Institut Hindu Dharma Negeri Denpasar, 2020)
Vocabulary is one of the English elements besides grammar, spelling, and pronunciation supporting English language skill such as listening, speaking, reading, and writing. Vocabulary is the first element that should be master before the learners going to other element. When the learners have mastered vocabulary, they will be able to produce many sentences in spoken and written form easily. On the other hand, when they lack of vocabulary, they will find difficulty in deliver their thought, even their opinion to other people. One of the teaching strategies to enhance students? vocabulary is using English Song. This paper aims at describing the use of English song in teaching English vocabulary for students. The method of this research was a qualitative research combination of seven several journals from abroad and within the country about teaching vocabulary with song. Although there are many reasons why songs can be considered a valuable teaching tool, there are some issues to consider.